A combined multiscale modeling and experimental study on surface modification of high-volume micro-nanoparticles with atomic accuracy. (1st June 2022) - Li, Zoushuang; Xiang, Junren; Liu, Xiao; Li, Xiaobo; Li, Lijie; Shan, Bin; Chen, Rong
Abstract: Surface modification for micro-nanoparticles at the atomic and close-to-atomic scales is of great importance to enhance their performance in various applications, including high-volume battery, persistent luminescence, etc. Fluidized bed atomic layer deposition (FB-ALD) is a promising atomic-scale manufacturing technology that offers ultrathin films on large amounts of particulate materials. Nevertheless, nanoparticles tend to agglomerate due to the strong cohesive forces, which is much unfavorable to the film conformality and also hinders their real applications. In this paper, the particle fluidization process in an ultrasonic vibration-assisted FB-ALD reactor is numerically investigated from micro-scale to macro-scale through the multiscale computational fluid dynamics and discrete element method (CFD-DEM) modeling with experimental verification. Various vibration amplitudes and frequencies are investigated in terms of their effects on the fluid dynamics, distribution of particle velocity and solid volume fraction, as well as the size of agglomerates. Results show that the fluid turbulent kinetic energy, which is the key power source for the particles to obtain the kinetic energy for overcoming the interparticle agglomeration forces, can be strengthened obviously by the ultrasonic vibration. Besides, the application of ultrasonic vibration is found to reduce the mean agglomerate size in the FB. This is bound to facilitate the heat transfer and precursor diffusion in the entire FB-ALD reactor and the agglomerates, which can largely shorten the coating time and improve the film conformality as well as precursor utilization. The simulation results also agree well with our battery experimental results, verifying the validity of the multiscale CFD-DEM model. This work has provided momentous guidance to the mass manufacturing of atomic-scale particle coating from lab-scale to industrial applications. Highlights: The highlights of our work are: A multiscale model coupling the CFD-DEM is established to study the effect of ultrasonic vibration on FB-ALD process. Ultrasonic vibration accelerates the fluid and particle velocities, leading to more agglomerate breakage and higher fluidization quality. Ultrasonic vibration-assisted FB-ALD is an effective high-volume atomic scale manufacturing method for energy materials.